The Mediating Effect of Good Governance on the Relationship Between Managerial Roles and Personal Development in West Sumatera Provincial Government - Indonesia - Sentosa, Ilham (2009)
One of the challenges faced by public sector managers particularly in Indonesia today is the problem of identifying and determining their roles, their personal development and how to effectively implement the concept of good governance in their organization. Given a dynamic changing and continuing insight into public organizational effectiveness, public sector managers are rethinking how best they could accomplish their roles in order to attain their organization roles and objective. This study examined the roles of public sector manager to their personal development. This study also examined the mediating roles of good governance in the relationship between managerial roles, development roles, strategic roles and personal development. In determining this relationship, a hypothetical model of the relationship between roles of public sector managers, good governance and personal development was developed. The results suggested that the managerial roles had positive and significant influence on personal development than the other two development roles and strategic roles. Empirical study supported the institutional theory approach (Scott, 2001) in the hypothesized model. The empirical findings confirmed that good governance has a significant and positive impact on the relationship between managerial roles, development roles and strategic roles to the personal development of public sector managers. This proved that the management system theory is supported whereby public sector manager roles served as an input, while good governance as a process and personal development as an output. Based on empirical findings, it is suggested that personal development should be referred as an ideal social behavior of public sector managers. Overall, the study supported the hypotheses that good governance plays a mediating role in the relationship between public sector manager roles and personal development. This is consistent with governance theory (Lynn, 2001). One particular contribution of this study is the development of structural equation model to determine the relationships between the roles of public sector managers, good governance and the personal development of public sector managers. In conclusion, an understanding of the constructs of public sector manager roles and is a prerequisite for better insight on personal development of the public sector managers. The results of the study of public sector manager roles allowed the managers to implement good governance and determine their personal development paths.